2002
DOI: 10.1093/rheumatology/41.7.741
|View full text |Cite
|
Sign up to set email alerts
|

Methotrexate in the treatment of rheumatoid arthritis. II. In vivo effects on bone mineral density

Abstract: No adverse effect of low-dose MTX (mean 10 mg/week) on bone formation in RA was found.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
22
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(27 citation statements)
references
References 13 publications
4
22
0
1
Order By: Relevance
“…In animal studies high-dose methotrexate has been shown to induce apoptosis and suppress proliferation of the growth plate chondrocytes as well as proliferation of the osteoblasts and preosteoblasts 30. However, low-dose methotrexate (5–20 mg/week) both in cross-sectional31 32 and longitudinal33 studies has not shown any negative effect of methotrexate on bone.…”
Section: Discussionmentioning
confidence: 99%
“…In animal studies high-dose methotrexate has been shown to induce apoptosis and suppress proliferation of the growth plate chondrocytes as well as proliferation of the osteoblasts and preosteoblasts 30. However, low-dose methotrexate (5–20 mg/week) both in cross-sectional31 32 and longitudinal33 studies has not shown any negative effect of methotrexate on bone.…”
Section: Discussionmentioning
confidence: 99%
“…The mode of destruction was not always definite, however: some subjects showed heterogeneous destruction within a joint, and a few showed unilateral destruction or a difference in the degree of destruction between left and right sides. 9,16,17 …”
Section: Discussionmentioning
confidence: 99%
“…Minaur, et al reported results in a prospective nonrandomized trial with 116 non-steroid-treated RA subjects that suggest that MTX is safe for bone health at a low dose (10-15 mg once weekly) 7,21 . A critical review of published reports suggests that most patients treated with low-dose MTX do not have an increased risk of MTX osteopathy 22 .…”
Section: Rheumatologymentioning
confidence: 99%